Analisis Hukum Bunga Bank Ditinjau dari Perspektif Maqashid Syariah - Isnaeni, Sya Rifah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
The background of this research is the exixtance of the difference opinion between ulama and moslem scholars about the law of interest in Islam, which is until now still not discovered the solusion opinion and it make interesting for the researcher to make a research about the object more deep and more wide. But the researcher will not use Islamic law perspective as analysis basic, the researcher will use the objectives of sharia as analysis basic.This research is limited by several problems as following: (1) Why bank interest is needed by conventional banks? And (2) How is the law of interest if observed from the objectives of syariah (maqashid sharia)?This research is a library research. In this research the researcher choose to use a conceptual approach because the purposes which need to be achieved trouhg this research is to result an Islamic law thought about the law of interest which is not being bounded by the opinions or theories launched by majority of the moslem scholar. So this research can originally refer to the objectives of the sharia as what has been agreed by majority of ulama.The results of this research there are: (1) the interest is a money amount addition which have to paid by bank to the costumer based on the loan percentage that given by bank to their customer. Bank interest is used for the Bank's operational costs, if there is no interest instrument, it is likely that the Bank will not be able to survive. And (2) there are three opinions of ulama’s law judgments about the law of interest, it is forbidden (haram), permitted (halal) and dubious (shubhat). If this law opinions observed based on the objevtives of sharia, the researcher can make a conclusion that the opinion which is permit the interest is the most according to the objectives of sharia, and it is related to the concept of hifz al-nafs (take care of soul) and hifz al-mâl(take care of property) than the opinion whih has been forbid the interest. The permitted law of interest in the concept of hifz al-nafs (take care of soul) can be located in the dharuriyah, hajiyah and tahsiniyah degrees. While The permitted law of interest in the concept ofhifz al-mâl(take care of property)can be located in the dharuriyah and hajiyah degrees. Keywords: Interest, Usury, Maqashid Sharia, hifz al-nafs (Take care of soul), hifz al-mâl (Take care of Property).